Predictors of atherosclerotic lesions of limb arteries according to cardioangiological screening of the adult population - R. A. Khokhlov; A. E. Gaydashev; N. M. Akhmedzhanov (Столичная издательская компания, 2015)
Aim. To study the predictors of atherosclerotic lesions of arteries identified through a multi-channel volume sphygmography (MCVS). Material and methods. Simultaneous survey of 441 rural residents over 40 years old was performed. Synchronous registration of blood pressure (BP) on four limbs using MCVS was fulfilled, and differences in systolic BP between arms (ΔSBParm) and legs (ΔSBPleg) were calculated. Ankle-brachial index (ABI) was also evaluated. │ΔSBParm│≥15 mm Hg or │ΔSBPleg│≥15 mm Hg or ABI≤0.9 were considered as the markers of atherosclerotic arterial disease. Results. A significant asymmetry of SBP (≥15 mmHg) was found in 7.7% [95% confidence interval (CI) 5.5-10.6%] of patients in the upper limbs and in 6.8% (95 % CI 4.89.6%) of patients in the lower extremities. The relative risk of asymmetry of SBP (≥15 mm Hg) in the upper limbs increased in hypertension and obesity, and in the lower limbs in men and diabetes. Various quantitative risk factors of the onset and progression of atherosclerosis (age, body mass index, waist circumference, blood glucose, BP level) had a positive correlation with the level of asymmetry of SBP on the limbs. Using MCVS and the appropriate combinations of features (SBP asymmetry or ABI≤0.9) allowed us at the stage of screening to find out blood flow disturbances in the arteries of the extremities in 14.7% (95% CI 11.7-18.4%) of patients. This detection frequency was significantly higher than that when using only ABI. Conclusion. Identification of significant SBP asymmetry (≥15 mm Hg) in the limbs may improve the diagnosis of atherosclerotic arterial disease at the stage of screening.